Does platform switching really prevent crestal bone loss around implants? - Yoshiyuki Hagiwara (Elsevier, 2010)
To maintain long-term implant stability, it is important to minimize bone loss around the implant. Several clinical studies have shown a mean marginal bone loss around dental implants of 1.5-2 mm in the first year after prosthetic restoration. Currently, concepts to prevent bone loss around dental implants have been reported as the platform switching (PLS). This technique use of prosthetic abutments with reduced width in relation to the implant platform diameter seems to have the greatest potential to limit the crestal resorption. However, there are only a few reports on the mechanism of action or the extent of bone loss prevention, and as such, it is difficult to say that the effect of PLS has been thoroughly examined. Excluding case reports, articles on PLS can be broadly categorized into: (1) radiographic evaluation of crestal bone level in humans, (2) histological and histomorphometrical analysis in animals, or (3) finite element analysis. This review revealed a shortage of published data for above three categories related PLS. Researchers have attempted to explain the mechanism of action of PLS; however, it is necessary to conduct further studies, including histological studies using animals, to clarify the mechanism fully.